PERENCANAAN MODEL BISNIS PADA START-UP “FEME.ID” MENGGUNAKAN METODE BUSINESS MODEL CANVAS (BMC) - Siti Muflikhatun; Retno Waluyo (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Business Model Canvas (BMC) is a business model with nine blocks that are used to plan a business model into a strong business strategy to be able to compete in the market. This research was conducted to plan a business model for the start-up